Kebebasan Berpendapat Menurut John Stuart Mill dan Relevansinya Bagi Kebebasan Pers di Indonesia (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
This article examines John Stuart Mill's concept of liberty of expression in his work, On Liberty, and its relevance to the current state of liberty of press in Indonesia. Using a qualitative approach through literature review, this research analyzes Mill's key ideas: individual liberty, liberty of thought and discussion, harm principle, and the dangers of the tyranny of the majority, and relates these to the actual reality of press freedom in Indonesia. The analysis shows that although the liberty of expression is constitutionally guaranteed, its practice remains constrained by repressive regulations such as the Electronic Information and Transactions Law (UU ITE), violence against journalists, and intimidation of critical media outlets. Mill emphasized the importance of distinguishing between the private and public spheres, the role of discussion in the search for truth, and the limitation of liberty only when it causes tangible harm. The conclusion is that Mill's liberal principles can serve as an ethical basis for reforming Indonesian democracy, particularly in strengthening legal protections and democratic culture to guarantee the liberty of press.